Corruption, privatisation and the distribution of income in Latin America - Antonio Rodriguez; Carlyn Ramlogan (Institute for Advanced Development Studies (INESAD), 2007)
This paper presents some new evidence on income inequality in Latin America over the period 1980-1999, examining in particular the relationship between corruption, privatisation and inequality. Using a panel data methodology, we find that a reduction in corruption is associated with a rise in inequality. This suggests that while privatisation removes industries from government influence and government corruption, it worsens income inequality as new owners strive for efficiency and profits. The paper highlights the fact that structural reform policies aimed primarily at achieving positive and increasing growth rates do not adequately address the income distribution problem.
Keywords: O15; O54; 330; Población; income inequality; corruption; privatisation; panel data; Latin America; instrumental variables.